2010
DOI: 10.1016/j.apgeochem.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater residence time and movement in the Maltese islands – A geochemical approach

Abstract: 12The Maltese Islands are composed of two limestone aquifers, the Upper and Lower

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…In agreement with the hydrological settings, tritium and SF 6 data suggest that the perched aquifers contain relatively young groundwater (Bakalowicz and Mangion, 2003;Stuart et al, 2010) This was confirmed by the presence of E. Coli, often at high concentrations, in 10 of the 12 perched aquifer sources sampled in this study (Stuart et al, 2010). The major ion chemistry is predominantly Ca + Mg bicarbonate, but also with high concentrations of Na and Cl (median ca.…”
Section: Perched Aquiferssupporting
confidence: 66%
See 3 more Smart Citations
“…In agreement with the hydrological settings, tritium and SF 6 data suggest that the perched aquifers contain relatively young groundwater (Bakalowicz and Mangion, 2003;Stuart et al, 2010) This was confirmed by the presence of E. Coli, often at high concentrations, in 10 of the 12 perched aquifer sources sampled in this study (Stuart et al, 2010). The major ion chemistry is predominantly Ca + Mg bicarbonate, but also with high concentrations of Na and Cl (median ca.…”
Section: Perched Aquiferssupporting
confidence: 66%
“…Since the islands rise to a maximum altitude of 239 m above sea level, the MSL aquifers are overlain by a thick unsaturated zone, typically from 40 to 120 m for boreholes sampled in this study (Stuart et al, 2010). In western parts of Malta, and over a large area of Gozo this zone is capped by the Blue Clay and Upper Coralline Limestone.…”
Section: Mean Sea Level (Msl) Aquifersmentioning
confidence: 99%
See 2 more Smart Citations
“…The BMM applied in this paper is usually appropriate for multi-layers aquifers (La Salle et al, 2012;Stuart et al, 2010). This model reveals the presence of "young" and "old" water bodies, in agreement with groundwater temperatures and only slightly influenced by the seasonal surface atmospheric conditions and by the tritium concentrations below 1-2 TU linked to an important ratio of pre-1950's water.…”
Section: Groundwater Flow Pathsmentioning
confidence: 73%